STRATEGI DINAS LINGKUNGAN HIDUP KOTA BANDAR LAMPUNG DALAM PENGELOLAAN SAMPAH RUMAH TANGGA: Studi Pada Kecamatan Bumi Waras Kota Bandar Lampung - Setiawati, Dina; Pramazuly, Ayu Nadia; Mosshananza, Hinfa (Jurnal Progress Administrasi Publik, 2025)
Waste is one of the critical issues in Indonesia that has not been adequately addressed. This reality contrasts with the fact that waste production and disposal are activities that continue in daily life. However, not many people are concerned about the ongoing issue of accumulating waste. Considering the problem of waste buildup, the strategies implemented by the Environmental Service are crucial in waste management in Indonesia, particularly in the city of Bandar Lampung. This is emphasized because Bandar Lampung is one of the cities with a high population density, particularly in the Bumi Waras District. The amount or volume of waste corresponds to the level of consumption of goods or materials used daily. This study employs a qualitative descriptive method, with data collected through observation, interviews, and documentation techniques. The analysis in this study is based on Koteen's (1991) strategy theory, which classifies strategies into three categories: Organizational Strategy, Program Strategy, and Resource Strategy. Based on the study's findings, household waste management by the Bandar Lampung City Environmental Service is considered to have been carried out effectively. However, there are still issues or obstacles in the program strategies and supporting resource strategies that prevent it from running optimally. It seems to be constrained by budget and the facilities needed for household waste management. Therefore, improvements and enhancements in this regard are necessary.   Keywords: Management: Household; Strategy; Waste